THE PATHOPHYSIOLOGY RELATIONSHIP OF HYPERTENSION AND RENAL HYPERTENSION - Kadir, Akmarawita (Universitas Wijaya Kusuma Surabaya, 2016)
Introduction : Hypertension is a disease with an incidence rate is still high around the world, most of the causes of hypertension is unknown (essential hypertension / primary hypertension), a small portion of hypertension caused by diseases acquired (secondary hypertension). The unknown cause of Hypertension causing complications of diseases that worsen it, eg kidney disease (renal disease), and can be a disease that actually cause hypertension becomes more severe (secondary hypertension). Pathophysiology of essentialÂ hypertension has been a lot of discussed, but the pathophysiology of renal disease which causes hypertension still needs to be explored, particularly on the relationship between primary hypertension and secondary hypertension (hypertension, kidney or renal hypertention). Kidney disease is a disease that cause hypertension via the mechanism of resistance increases blood circulation to the kidneys and a decrease in the glomerular capillary function which resulted in the release of an important substance-substance such as renin, angiotensinogen, angiotensin I, angiotensin II, angiotensin converting enzyme (ACE) inhibitors, aldosterone, bradykinin, nitric oxide (NO), which in turn causes increase blood pressure (hypertension). Hypertension proved to be a feedback mechanism to suppress the high renin, renin suppression doesnât mean anything if kidney disease not treated properly, and even cause permanently hypertension or even getting worse. The purpose of this article was to determine the pathophysiology of hypertension, renal hypertension in particular, and how the relationship between hypertension and renal hypertension (secondary).